2016
DOI: 10.3102/0091732x16677020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Century of Advancements in the Science of Learning

Abstract: The past century has yielded a plethora of advancements in the science of learning, from expansions in the theoretical frames that undergird education research to cultural and contextual considerations in educational practice. The overarching purpose of this chapter is to explore and document the growth and development of the science of learning using a tripartite approach. The authors first provide an overview of definitions of learning that have been forwarded in the extant literature, with particular emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 166 publications
0
17
0
Order By: Relevance
“…Wong et al (2019) reasoned that a good understanding of how learning occurs, how learning can be supported, and how student characteristics influence learning is needed if the goal of LA is to understand and optimise learning. Based on a recent review of papers published in the Review of Educational Research (RER) journal over the last century, Murphy and Knight (2016) found that learning sciences have been guided by three predominant theoretical lenses: behavioral, cognitive, and contextual (Wong et al,…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al (2019) reasoned that a good understanding of how learning occurs, how learning can be supported, and how student characteristics influence learning is needed if the goal of LA is to understand and optimise learning. Based on a recent review of papers published in the Review of Educational Research (RER) journal over the last century, Murphy and Knight (2016) found that learning sciences have been guided by three predominant theoretical lenses: behavioral, cognitive, and contextual (Wong et al,…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while the sociocognitive perspective is situated at the intersection of both social constructivist and cognitive frameworks, it uniquely grounds the vital and influential role of the teacher in enhancing students’ comprehension through discussion (Bandura, ). Indeed, teachers can support students’ comprehension by modeling critical‐analytic thinking, challenging students with misconceptions, and prompting them to elaborate their thinking aloud within small‐group discussions (Murphy & Knight, ; Wei & Murphy, in press). In sum, the weaving of such robust and comprehensive foundations provides a strong theoretical foundation for the prediction that small‐group classroom discussions can facilitate students’ reading comprehension.…”
Section: Theoretical Foundations Relating Classroom Discussion To Reamentioning
confidence: 99%
“…Based on a recent review of papers published in Review of Educational Research (RER) journal over the last century, Murphy and Knight (2016) found that learning sciences have been guided by three predominant theoretical lenses: behavioural, cognitive, and contextual. The authors used the word "lenses" to analogously refer to the theories that researchers use.…”
Section: Evolution Of Learning Theoriesmentioning
confidence: 99%
“…Theories that developed from the contextual lens included social constructivism and social learning theory. Murphy and Knight (2016) concluded that the shift in theoretical lens occurs when findings from new studies cannot be explained by the existing lens.…”
Section: Evolution Of Learning Theoriesmentioning
confidence: 99%
See 1 more Smart Citation